SARS-CoV-2-Specific Memory T Lymphocytes From COVID-19 Convalescent Donors: Identification, Biobanking, and Large-Scale Production for Adoptive Cell Therapy - Ferreras, C.; Pascual-Miguel, B.; Mestre-Durán, C.; Navarro-Zapata, A.; Clares-Villa, L.; Martín-Cortázar, C.; De Paz, R.; Marcos, A.; Vicario, J. L.; Balas, A.; García-Sánchez, F.; Eguizabal, C.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Syndrome coronavirus 2 (SARS-CoV-2) pandemic is causing a second outbreak significantly delaying the hope for the virus’ complete eradication. In the absence of effective vaccines, we need effective treatments with low adverse effects that can treat hospitalized patients with COVID-19 disease. In this study, we determined the existence of SARS-CoV-2-specific T cells within CD45RA– memory T cells in the blood of convalescent donors. Memory T cells can respond quickly to infection and provide long-term immune protection to reduce the severity of COVID-19 symptoms. Also, CD45RA– memory T cells confer protection from other pathogens encountered by the donors throughout their life. It is of vital importance to resolve other secondary infections that usually develop in patients hospitalized with COVID-19. We found SARS-CoV-2-specific memory T cells in all of the CD45RA– subsets (CD3+, CD4+, and CD8+) and in the central memory and effector memory subpopulations. The procedure for obtaining these cells is feasible, easy to implement for small-scale manufacture, quick and cost-effective, involves minimal manipulation, and has no GMP requirements. This biobank of specific SARS-CoV-2 memory T cells would be immediately available “off-the-shelf” to treat moderate/severe cases of COVID-19, thereby increasing the therapeutic options available for these patients.